Direct sampling method for anomaly imaging from scattering parameter. (July 2018) - Park, Won-Kwang
Abstract: In this paper, we develop a fast imaging technique for small anomalies located in homogeneous media from scattering parameter data measured at dipole antennas. Based on the representation of scattering parameters when an anomaly exists, we design a direct sampling method (DSM) for imaging an anomaly and establishing a relationship between the indicator function of DSM and an infinite series of Bessel functions of integer order. Simulation results using synthetic data at f = 1 GHz of angular frequency are illustrated to support the identified structure of the indicator function.